Lead analysis in paints for high impact control in homes. Issue 33 (5th August 2019) - Ansín, Andrés; Galietta, Giovanni; Botasini, Santiago; Méndez, Eduardo
Abstract : Only samples that tested positive for lead by the dust wipe method (DWM) were accurately measured by the electrochemical method (EChem) and identified by FTIR. Abstract : Environmental lead has been successfully abated in most countries due to the ban of lead compounds in fuels. However, little action has been taken to mitigate other sources of lead contamination. As of 2018, only 71 countries have placed additional legal restrictions on the use of lead in paints. However, lead inside homes is still a relevant problem that it is difficult to control because homes are private property in most countries. Hence, suitable methods for in situ analysis that provide simple but precise means of lead detection and quantification are in demand. An interdisciplinary group was created in Uruguay for the in-home detection of lead in painted walls, doors, and windows. Lead is detected by the dust wipe method, analysed by a decentralised electrochemical method on bismuth film electrodes, and further characterized by FTIR. Within the same inspection event, children in contaminated homes are directed to medical assistance and repainting of the contaminated source is scheduled. The use of decentralised analyses provides an immediate response to this problem at an affordable cost for massive inspections.